2014
DOI: 10.1099/mic.0.081216-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the region of Pseudomonas aeruginosa ParA that is important for dimerization and interactions with its partner ParB

Abstract: Pseudomonas aeruginosa ParA belongs to a large subfamily of Walker-type ATPases acting as partitioning proteins in bacteria. ParA has the ability to both self-associate and interact with its partner ParB. Analysis of the deletion mutants defined the part of the protein involved in dimerization and interactions with ParB. Here, a set of ParA alanine substitution mutants in the region between E67 and L85 was created and analysed in vivo and in vitro. All mutants impaired in dimerization (substitutions at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
(122 reference statements)
2
19
0
Order By: Relevance
“…These authors mapped the ParB⅐ParA interacting region to within an interval equivalent to residues 89 -105 of ␦ 2 , by yeast two-hybrid and immunoprecipitation assays (40). This is in good agreement with the ⅐␦ interacting region reported here (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These authors mapped the ParB⅐ParA interacting region to within an interval equivalent to residues 89 -105 of ␦ 2 , by yeast two-hybrid and immunoprecipitation assays (40). This is in good agreement with the ⅐␦ interacting region reported here (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…To reconcile the apparent discrepancy between the crystal structure of ␦ 2 ⅐ATP␥S⅐Mg 2ϩ (15), our data (Fig. 5B), and those published by other groups (39,40), we propose that the bacterial or yeast two-hybrid assays cannot discriminate between the monomer and the dimer interface and that the authors were mapping the dimer-dimer interface (see Fig. 7A, center).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous biochemical studies identified regions in ParB proteins that are involved in binding to their partner ParA proteins (Bartosik et al 2014;Volante and Alonso 2015). Work by Volante and Alonso (2015) revealed that pSM19035 plasmid ParB (also called ω) interacts with residues 88-119 in its partner, ParA (also called δ).…”
Section: Resultsmentioning
confidence: 99%